Investigating the Formation Mechanism of Arene Ruthenium Metallacycles by NMR Spectroscopy. Issue 33 (12th September 2014) - Garci, Amine; Gupta, Gajendra; Dalvit, Claudio; Therrien, Bruno
Abstract: The stereochemical properties of twelve dinuclear arene ruthenium complexes have been studied in solution. The dinuclear complexes of the general formula [( p ‐cymene)2 Ru2 (OO∩OO)(L n )2 ](CF3 SO3 )2 (OO∩OO = oxalato, 2, 5‐dioxido‐1, 4‐benzoquinonato, 5, 8‐dioxido‐1, 4‐naphthoquinonato; L n = 4‐phenylpyridine, 4‐styrylpyridine, 4‐methylpyridine, 4‐ tert ‐butylpyridine) have been isolated as mixtures of the cis and trans isomers. All of the complexes showed lability of the pyridyl‐based ligands (L n ) in solution and rapid exchange between the cis and trans isomers. The equilibrium between the cis and trans isomers was confirmed by 1 H NMR spectroscopy, and the intermediate species were identified and, thus, provided valuable insights into the formation mechanism of arene ruthenium metalla‐assemblies. Abstract : The stereochemical properties of twelve dinuclear arene ruthenium complexes have been studied in solution by NMR spectroscopy. All complexes showed lability of the pyridyl‐based ligands in solution and rapid exchange between the cis and trans isomers. The intermediate species have been identified and, thus, provided insights into the formation mechanism of arene ruthenium metalla‐assemblies.